PD-L1 expression by dendritic cells is a key regulator of T-cell immunity in cancer - Oh, Soyoung A; Wu, Dai-Chen; Cheung, Jeanne; Navarro, Armando; Xiong, Huizhong; Cubas, Rafael; Totpal, Klara; Chiu, Henry; Wu, Yan; Comps-Agrar, Laetitia; Leader, Andrew M; Merad, Miriam; et al. (Nature cancer, 2020)
Inhibiting the programmed death-1 (PD-1) pathway is one of the most effective approaches to cancer immunotherapy, but its mechanistic basis remains incompletely understood. Binding of PD-1 to its ligand PD-L1 suppresses T-cell function in part by inhibiting CD28 signaling. Tumor cells and infiltrating myeloid cells can express PD-L1, with myeloid cells being of particular interest as they also express B7-1, a ligand for CD28 and PD-L1. Here we demonstrate that dendritic cells (DCs) represent a critical source of PD-L1, despite being vastly outnumbered by PD-L1 macrophages. Deletion of PD-L1 in DCs, but not macrophages, greatly restricted tumor growth and led to enhanced antitumor CD8 T-cell responses. Our data identify a unique role for DCs in the PD-L1-PD-1 regulatory axis and have implications for understanding the therapeutic mechanism of checkpoint blockade, which has long been assumed to reflect the reversal of T-cell exhaustion induced by PD-L1 tumor cells.